Mental health literacy: a comparative study on stigmatizing attitude and help-seeking behavior towards mental disorders between adolescents and adults - Amal M. I. Goda; Salwa A. Abd Elhamid; Ghada O. Wassif (Journal of the Egyptian Public Health Association)
Abstract Background Mental health awareness has the potential to contribute to the prompt identification and effective management of mental disorders. The negative perception connected to mental conditions presents a significant challenge for individuals seeking mental health services and the professionals providing them. This study aims to compare mental health literacy—encompassing knowledge, attitudes, and behaviors—between adults and adolescents attending Ain Shams University Hospitals’ outpatient clinics and identify the socio-demographic factors that could predict these components. Methods The present survey was carried out during the years 2022–2023 on 369 individuals, who were 11 years or older. An Arabic questionnaire, validated and tested for reliability, was employed to evaluate knowledge, attitudes, and behaviors related to mental disorders. The tools consisted of three validated scales: the Mental Health Knowledge Schedule (MAKS), the Community Attitudes towards Mental Illness (CAMI), and the Reported and Intended Behavior Scale (RIBS). Results Adults demonstrated significantly higher knowledge scores (46.33 ± 4.69 vs. 43.16 ± 4.92, p ≤ 0.01) and behavior scores (16.66 ± 3.56 vs. 15.53 ± 3.71, p ≤ 0.01), while adolescents exhibited more favorable attitudes (99.03 ± 17.43 vs. 90.74 ± 11.78, p ≤ 0.01). Higher knowledge was associated with being female, having a university education, living in urban areas, and being employed. Favorable attitudes were linked to adolescents, males, rural residents, and lower educational levels. At the same time, positive behaviors were associated with being female, having a university education, living in urban areas, being employed, and knowing someone with a mental illness. Regression analysis highlighted education and urban residence as consistent predictors across all mental health literacy components, with employment and familiarity with mental illness further enhancing behavior scores. Conclusion This study highlights significant differences in mental health literacy between adults and adolescents, with adults exhibiting higher knowledge and behavior scores and adolescents demonstrating more favorable attitudes. Socio-demographic factors, particularly education, urban residence, and employment, emerged as consistent predictors influencing knowledge, attitudes, and behaviors. These findings underscore the need for targeted interventions, such as incorporating mental health education into curricula, launching stigma-reduction campaigns, and improving access to mental health services, particularly in rural areas.